High-toughness ultrahigh-strength stainless steel bar and preparation method thereof
By adopting a composite strengthening method of aluminum and Nb elements in stainless steel, combined with high-temperature refining and fine heat treatment, the problem of insufficient strength and toughness of existing stainless steel is solved, and the preparation of ultra-high strength and high-toughness stainless steel rods is realized, which is suitable for high-demand application scenarios.
Patent Information
- Application Number
- CN202311259060.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
The existing precipitated hardened stainless steel has shortcomings in strength and toughness, especially in application scenarios where long life and safety requirements are more demanding.
Aluminum elements are used as the main reinforcement element, combined with the addition of Nb elements, and the low content of impurity elements is controlled through the composite method of precipitation hardening and carbide reinforcement, and the component design is optimized to improve the tensile strength and fracture toughness of stainless steel. At the same time, through high-temperature refining and fine heat treatment, the material is ensured to be consistent and corrosion resistance.
It realizes ultra-high strength (tensile strength ≥1550MPa) and high toughness (fracture toughness KIC ≥110MPa·m1/2) of stainless steel rods, while ensuring the heterogeneous consistency of the material and good corrosion resistance. It is suitable for high-demand aerospace, petroleum, chemical and other fields.
Smart Images

Figure BDA0004472162110000111 
Figure BDA0004472162110000121 
Figure BDA0004472162110000131
Abstract
Description
Technical Field
[0001] The invention belongs to the field of stainless steel bar processing, and in particular relates to a high-toughness ultra-high-strength stainless steel bar and a preparation method thereof. Background Art
[0002] Precipitation hardening stainless steel is widely used in some key load-bearing structures in the aerospace field due to its high strength and corrosion resistance. In addition, this high-performance stainless steel is also in high demand in the medical, oil and gas, energy, automotive, hand tools, consumer goods and other fields.
[0003] The commonly used martensitic precipitation hardening stainless steel is 05Cr17Ni4Cu4Nb (GB / T1220-2007). This steel is designed with low C, high Cr and Cu. Its strength, toughness and corrosion resistance are better than those of general martensitic stainless steel, but its process performance is relatively poor, mainly because the steel contains 5-10% delta ferrite (ferrite formed at high temperature). The presence of delta ferrite will affect the thermoplasticity of the steel, reduce the strength of the steel and deteriorate the transverse toughness of the steel, and also reduce the corrosion resistance of the steel.
[0004] Chinese patent CN200810034926.7 discloses "a kind of martensitic precipitation hardening stainless steel for structural parts and its manufacturing method", the chemical composition includes: C≤0.05wt%, Cr: 13.50~15.50wt%, Cu: 2.5~4.0wt%, Ni: 3.0~5.0wt%, Nb+Ta: 0.15~0.40wt%, N: 0.010~0.040wt%, V: 0.050~0.15wt%, Si≤0.80wt%, Mn≤1.00wt%, P≤0.025wt%, S≤0.010wt%, the balance is Fe and unavoidable impurities. The tensile strength of stainless steel reaches 1390Mpa, the yield strength reaches 1300Mpa, the elongation reaches 15%, and the shrinkage reaches 48% (transverse performance). The precipitation hardening stainless steel bar reinforced with Cu element and its preparation method are used to manufacture high-strength and corrosion-resistant precipitation hardening stainless steel bar through vacuum melting ingot, forging blanking, extrusion deformation, etc. However, in the face of more stringent requirements for long life and safety, the above stainless steel has obvious problems of insufficient strength.
[0005] Chinese patent CN201610591787.2 discloses "a high-strength and high-toughness stainless steel material and its preparation method". The stainless steel, measured in weight percentage, includes C≤0.05%, Si≤1.0%, Mn≤1.0%, Cr: 12.25-13.25%, Ni: 7.5-8.5%, Mo: 2.0-2.5%, Al: 0.9-1.35%, and the balance is Fe. The Al element is used to strengthen precipitation hardening, and high-strength stainless steel bars are obtained through vacuum induction smelting, electroslag remelting and forging. Although its tensile strength can reach more than 1500MPa, the obtained stainless steel has a large difference in longitudinal and transverse impact energy, and the measured fracture toughness KIC is less than 90MPa·m 1 / 2 . Summary of the invention
[0006] The object of the present invention is to provide a high-toughness ultra-high strength stainless steel bar and a preparation method thereof, wherein the obtained stainless steel bar has both ultra-high strength and high toughness, and its tensile strength is ≥1550MPa, and its fracture toughness KIC is ≥110MPa·m 1 / 2 At the same time, the consistency of the mechanical properties of the material is guaranteed, the difference between the transverse and longitudinal impact energy AkU is ≤11%, it has good corrosion resistance and is easy to process. It can be used in aerospace, petroleum, chemical, energy and power fields that have high requirements for strength, toughness and corrosion resistance.
[0007] To achieve the above object, the technical solution of the present invention is:
[0008] The high-toughness ultra-high-strength stainless steel bar has the following components by weight: C: 0.025-0.045%, Cr: 12.00-13.00%, Mo: 1.8-2.3%, Al: 0.90-1.10%, Nb: 0.01-0.02%, S≤0.0015%, P≤0.01%, Si≤0.10%, Mn≤0.10%, N≤0.0015%, Ti≤0.01%, H≤0.0001%, O≤0.0008%, the remainder includes Fe and other inevitable impurities, and at the same time satisfies: Ni=(Cr+Mo)×0.45+Al×2.15.
[0009] Furthermore, the balance is Fe and other inevitable impurities.
[0010] The content of delta ferrite in the microstructure of the stainless steel bar of the present invention is ≤0.5%, and the grain size is ≥7 levels.
[0011] The stainless steel bar of the present invention has a tensile strength of ≥1550MPa, a yield strength of ≥1415MPa, an elongation of ≥15%, a surface shrinkage of ≥65%, a transverse and longitudinal impact energy AkU difference of ≤11%, and a fracture toughness KIC of ≥110MPa·m 1 / 2 .
[0012] In the composition design of the present invention:
[0013] Practice shows that under conventional processing methods, precipitation hardening stainless steel is difficult to reach a higher strength of more than 1450MPa by simply strengthening with Cu element. Therefore, the present invention uses aluminum (Al) element as the main strengthening element for precipitation hardening strengthening. The main role of Al in martensitic precipitation hardening stainless steel is precipitation aging strengthening; through solution aging heat treatment, dispersed β-NiAl phase can be precipitated in the martensitic matrix to produce precipitation hardening and strengthen the steel. At the same time, aluminum can form a dense oxide film Al2O3 on the steel surface to improve the oxidation resistance of stainless steel; aluminum is also a ferrite forming element, and its ability to promote ferrite formation is about 2.53 times that of chromium, so the aluminum content cannot be too high; the aluminum content of the present invention is controlled at 0.90-1.10%.
[0014] Studies have shown that in order to improve the toughness of stainless steel under ultra-high strength conditions (≥1550MPa), it needs to have very high purity and fine and uniform grain size.
[0015] To achieve the above-mentioned purpose, the control scheme of the molten steel purity of the present invention is: strictly control the content of impurity elements: S≤0.0015%, P≤0.01%, Si≤0.10%, Mn≤0.10%, N≤0.0015%, Ti≤0.01%, H≤0.0001%, O≤0.0008%.
[0016] Sulfur (S): It exists in the form of FeS in steel, which will cause the hot brittleness of steel. The melting point of FeS is 1193℃, while the melting point of the eutectic composed of Fe and FeS is only 985℃. Liquid Fe and FeS can be infinitely soluble in each other, but the solubility of FeS in solid iron is very small, only 0.015-0.020%. Therefore, when the sulfur content of steel exceeds 0.020%, due to segregation during the cooling and solidification process of the molten steel, Fe-FeS is distributed in the grain boundaries in a network in the form of a low-melting-point eutectic. The hot working temperature of steel is between 1150 and 1200℃. At this temperature, the eutectic at the grain boundary has melted. When the steel is compressed, it causes the rupture of the grain boundary. This is the "hot brittleness" of the steel. When the oxygen content in the steel is high, the melting point of the eutectic formed by FeO and FeS is lower, only 940℃, which aggravates the "hot brittleness" phenomenon of the steel. In addition, sulfur will significantly reduce the welding performance of steel, cause high temperature cracking, and produce many pores and looseness in the metal weld, thereby reducing the strength of the weld. When the sulfur content exceeds 0.06%, the corrosion resistance of the steel is significantly deteriorated. Therefore, the sulfur content of the present invention is controlled to be below 0.0015%.
[0017] Phosphorus (P): In stainless steel, it can be completely dissolved in ferrite, improving the strength and hardness of ferrite. However, at room temperature, it causes a sharp drop in the plasticity and toughness of steel, resulting in low-temperature brittleness, a phenomenon known as cold brittleness. Generally speaking, phosphorus is a harmful element in steel, mainly precipitating the brittle compound Fe3P, which increases the brittleness of steel, especially at low temperatures. Therefore, the phosphorus content of the present invention is controlled to be below 0.01%.
[0018] Silicon (Si): It is mainly used as a deoxidizer during smelting, and can strengthen the matrix, improve the corrosion resistance and high temperature oxidation resistance of steel. However, too high a silicon content will lead to the precipitation of harmful phases, reducing the hot working performance and toughness of the steel. The inventors have found through experiments that when the Si content in the steel involved in the present invention is higher than 0.1%, the fracture toughness of the steel in the ultra-high strength state will drop sharply. Therefore, the present invention regards silicon as a harmful element and controls the content to be below 0.10%.
[0019] Manganese (Mn): It is an austenite stabilizing element that can expand the austenite phase. It is a good deoxidizer and desulfurizer. Industrial steel usually contains a certain amount of manganese. In stainless steel, manganese can replace part of nickel to stabilize austenite, reduce production costs, and increase the nitrogen content in steel to ensure the strength of steel. However, too high manganese content will greatly reduce the corrosion resistance of steel, especially the ability to resist pitting and intergranular corrosion. Therefore, the present invention also regards manganese as a harmful element, and the content is controlled below 0.10%.
[0020] Titanium (Ti): It is the most effective strengthening alloy element in stainless steel. Generally, adding an appropriate amount of titanium has a significant aging strengthening effect, mainly forming a Ni3Ti strengthening phase during the aging process. However, titanium is very easy to form sharp quadrilateral Ti (C, N) inclusions with C and N in steel, and can also form hard polygonal (Ti, Mo) C inclusions with Mo, thereby seriously reducing the fracture toughness KIC value of stainless steel. Therefore, the present invention uses titanium as a harmful element and controls the content to be below 0.01%.
[0021] Nitrogen (N): It exists in the form of interstitial atoms in the unit cell. Due to the large difference in atomic size, it is more conducive to the solid solution strengthening of steel. As an austenite stabilizing element, N is about 25 times more effective than Ni in expanding and stabilizing austenite. Its solid solubility in austenite is much higher than that of ferrite. Usually, there is a small amount of ferrite in conventional stainless steel. As the carbon content decreases, the ferrite content will increase, resulting in a decrease in the strength, plasticity and toughness of the stainless steel. In addition, when a certain amount of Ti element exists in stainless steel, N is very likely to form hard TiN or Ti (C, N) inclusions with it, thereby seriously reducing the toughness of the stainless steel. Therefore, the nitrogen content of the present invention is controlled to be below 0.0015%.
[0022] Hydrogen (H): It is a harmful element in steel. Hydrogen dissolved in steel can cause defects such as hydrogen embrittlement and white spots. Hydrogen has a very low solubility in solid steel. It dissolves into molten steel at high temperature. When cooling and solidifying, it has no time to escape and accumulates in the steel matrix to form high-pressure fine pores, which sharply reduce the plasticity, toughness and fatigue strength of the steel. In severe cases, it can cause cracks and brittle fractures. Therefore, the hydrogen content of the present invention is controlled to be below 0.0001%.
[0023] Oxygen (O): It will have an adverse effect on the mechanical properties of steel. Not only the concentration of oxygen, but also the amount, type and distribution of oxygen-containing inclusions have a very important influence. Such inclusions refer to metal oxides, silicates, aluminates, oxygen-containing sulfides and similar inclusion compounds. Deoxidation is required in steelmaking because during solidification, oxygen and carbon in the solution react to produce carbon monoxide, which can cause bubbles. In addition, during cooling, oxygen can precipitate from the solution as FeO, MnO and other oxide inclusions, thereby weakening its hot or cold workability, as well as ductility, toughness, fatigue strength and mechanical processing properties of steel. Therefore, the oxygen content of the present invention is controlled below 0.0008%.
[0024] In order to ensure good toughness while having ultra-high strength (≥1550MPa), in addition to requiring very low impurity content and high purity, the steel also needs to have a fine and uniform grain structure (≥7 grade). To this end, the present invention retains a small amount of carbon element in the steel and adds a small amount of Nb element to form carbide pinning to ensure that the grains will not grow during the heat treatment process.
[0025] Carbon (C): It is an interstitial solid solution element that can significantly improve the matrix strength of steel. It can stabilize austenite, inhibit the formation of delta ferrite, and form fine dispersed carbides to strengthen the matrix. However, its solubility in austenite and ferrite is limited. Too high a carbon content will cause precipitation of M during heat treatment. 23 C6 carbides reduce the intergranular corrosion resistance of steel. However, too low a carbon content can easily lead to a decrease in the precipitation temperature of carbides. During solution heat treatment, the grains lacking carbide pinning are prone to grow due to the premature dissolution of carbides, thereby affecting the impact toughness of stainless steel. Therefore, the carbon content in the present invention is controlled at 0.025-0.045%.
[0026] Niobium (Nb): It is a strong carbide-forming element, which can form fine, dispersed NbC, Nb(C,N) and other carbides with carbon in the matrix. These precipitated phases have good stability, which plays an important role in maintaining the stability of the subgrain structure and improving the long-lasting strength of steel, and greatly improves the tempering resistance of steel. Too high Nb content will increase the cost, and too low Nb content will lead to a decrease in the precipitation temperature of carbides. During the solution heat treatment, the carbides will dissolve in advance, resulting in the grains lacking carbide pinning to grow easily, thereby affecting the impact toughness of stainless steel. Therefore, the niobium content of the present invention is controlled at 0.01-0.02%.
[0027] In order to achieve good corrosion resistance, elements such as Cr, Ni, and Mo are added in the present invention.
[0028] Chromium (Cr): It is a ferrite stabilizing element. It mainly improves the corrosion resistance and oxidation resistance of stainless steel. Studies have shown that steel must contain at least 10.5% Cr to form a stable passivation film that protects the steel from atmospheric corrosion. The corrosion resistance of stainless steel increases with the increase of Cr content. However, too high Cr content will promote the formation of delta high-temperature ferrite phase, reduce the hot working performance of stainless steel and the longitudinal and transverse consistency at room temperature, and easily lead to the occurrence of metal segregation during smelting. Therefore, the chromium content of the present invention is controlled at 12.00-13.00%.
[0029] Molybdenum (Mo): It is beneficial to the strength, toughness and corrosion resistance of martensitic stainless steel. When molybdenum-rich precipitates are precipitated in the early stage of aging, they can not only play a strengthening role, but also maintain the toughness of steel, which plays an important role in strengthening and toughening steel. The presence of molybdenum can also hinder the precipitation of precipitated phases on the original austenite grain boundaries, avoid intergranular fracture, and improve the fracture toughness of steel. In some reducing media, molybdenum can also promote the passivation of Cr. Therefore, molybdenum can improve the corrosion resistance of chromium-nickel stainless steel in some reducing acids, such as sulfuric acid, hydrochloric acid, phosphoric acid and some organic acids, and can effectively inhibit the pitting corrosion tendency of chloride ions on steel, and improve the ability to resist intergranular corrosion. Since molybdenum, like nickel, is also an austenite-forming element, the molybdenum element cannot be excessive. Excessive addition will generate residual austenite, thereby affecting the tensile strength. Therefore, the molybdenum content of the present invention is controlled at 1.80-2.30%.
[0030] Nickel (Ni): It is an austenite stabilizing element that can expand the austenite phase region, thereby ensuring that stainless steel has good plastic deformation characteristics. Nickel can improve the composition, structure and performance of the chromium oxide film, thereby improving the corrosion resistance and oxidation resistance of stainless steel, and can also significantly reduce the cold working hardening tendency of stainless steel. In the present invention, a part of the nickel is combined with the aluminum element to form, which is the main strengthening means. In addition, nickel can effectively reduce the δ ferrite content. Since a large number of studies have shown that the δ ferrite content is the main reason for the large longitudinal and transverse differences in mechanical properties such as tensile strength and fracture toughness, in order to improve the isotropic consistency of the mechanical properties of the present invention. It is necessary to reduce the δ ferrite content as much as possible (≤0.5%). The present invention controls the nickel content to satisfy Ni=(Cr+Mo)×(0.42~0.45)+Al×2.15%, ensures that a part of the nickel is combined with the aluminum element to form a β-NiAl phase, and controls the nickel content of this part to Ni=Al×2.15% according to the atomic molar ratio of nickel to aluminum. The second part is solid solution in the matrix, and the ratio between nickel and ferrite forming elements needs to be considered. The inventors of the present invention have found that controlling Ni=(Cr+Mo)*(0.42-0.45) can well control the precipitation of delta ferrite.
[0031] The method for preparing the high-toughness ultra-high-strength stainless steel bar of the present invention comprises the following steps:
[0032] 1) Smelting and casting
[0033] According to the above composition smelting, raw iron with purity ≥ 99.9% and other pure metals are used as furnace charge, and the charge is melted by induction heating in a vacuum environment below 3Pa. The molten steel needs to be continuously stirred by electromagnetic + gas mixed stirring in a high-temperature refining stage of 1500-1600℃. Subsequently, the high-purity molten steel obtained above is poured into a cylindrical ingot mold in a vacuum environment to obtain an electrode rod;
[0034] The electrode rod is purified in a copper crucible in a vacuum environment below 5 Pa by melting and solidifying. During the purification process, the inner and outer walls of the crucible are cooled by a composite cooling method of air cooling and water cooling to obtain a stainless steel ingot.
[0035] 2) Billet forging
[0036] The stainless steel ingot is heated to 1200-1250°C and kept warm for ≥15h, and then forged to obtain an intermediate forging billet;
[0037] 3) Forging or rolling
[0038] The intermediate forging billet is heated to 1050-1150°C and kept at this temperature for 3-5 hours, and the stainless steel bar is obtained by forging or rolling, and the total deformation ratio of the finished product is ≥6%;
[0039] 4) Solution treatment and cooling
[0040] The solution temperature is 910-940℃, the solution time is ≥1h, after the heat preservation, it is taken out of the furnace and cooled to the martensitic transformation end temperature M f Below, M f =M s -120, Ms=1317-45Cr-62Ni-30Mo-15Nb+20Al;
[0041] 5) Aging heat treatment
[0042] The aging temperature is 505-545℃, and the aging time is 1-10h. After the insulation is completed, the steel is taken out of the furnace and air-cooled to room temperature.
[0043] In the process design of the present invention:
[0044] In order to obtain high-purity ingots, the measures taken are mainly:
[0045] 1) In order to reduce the inclusions of type A (sulfide) and type C (silicate), high-purity raw iron with ultra-low S content and pure metal elements are used as the charge, and the charge is melted by induction heating in a vacuum environment below 3Pa.
[0046] 2) In order to quickly and thoroughly remove oxygen and nitrogen from the molten steel and reduce Class B (oxides) and Class D (spherical oxides and nitrides) inclusions, the molten steel needs to be continuously stirred using an electromagnetic + gas mixed stirring method during a high-temperature refining stage at 1500-1600°C.
[0047] 3) To avoid gas pollution, the high-purity molten steel obtained above is poured into a cylindrical steel ingot mold in a vacuum environment to obtain an electrode rod.
[0048] 4) To further improve the purity of the steel, the electrode rod is purified by melting and solidifying in a copper crucible in a vacuum environment below 1.5 Pa.
[0049] 5) During the purification process, the inner and outer walls of the crucible are cooled by inert gas and laminar water respectively to improve the cooling efficiency, so that the molten steel in the molten pool is quickly cooled and solidified, thereby obtaining a high-purity, defect-free, dense, fine-grained steel ingot.
[0050] In the preparation method of the present invention, in order to reduce the delta ferrite produced during the production process and improve the hot working performance of the material and the longitudinal and transverse consistency at room temperature, the measures taken mainly include:
[0051] During the open forging process, the ingot is heated to 1200-1250℃ and kept warm for no less than 15 hours. The residual δ ferrite generated by non-equilibrium solidification in the ingot is eliminated by solid high temperature equilibrium diffusion, and then open forging is performed to obtain the intermediate billet. This can effectively control and eliminate the δ ferrite in the matrix.
[0052] In the preparation method of the present invention, in order to improve strength and toughness, it is necessary to obtain a fine and uniform grain structure, and the measures taken are mainly:
[0053] 1) The intermediate forging billet is heated to 1050-1150°C and fully deformed by forging or rolling, and the total deformation ratio of the finished product is ≥6.
[0054] 2) When the product is subjected to solution heat treatment, in order to ensure that the grains are fully recrystallized and do not grow, the solution temperature is controlled at 910-940°C and the holding time is not less than 1 hour. Low temperature will affect the solution effect and reduce the uniformity of the structure. Too high temperature will lead to coarse grains and affect the plasticity and toughness of the material.
[0055] Since the alloying elements and contents of the present invention are relatively high, and the martensitic transformation temperature is relatively low, if the cooling after solid-state heat treatment is insufficient, a large amount of residual austenite will exist in the steel, which will reduce the strength of the steel. Therefore, the present invention strictly controls the temperature after cooling out of the furnace to be within the martensitic transformation end temperature M. f However, the martensitic transformation temperature obtained according to the existing martensitic transformation temperature calculation formula has a large error in the present invention. Therefore, the martensitic transformation end temperature M calculated according to the previous calculation formula is f If the temperature is controlled, there may be insufficient cooling. After research, the present invention corrects the calculation formula of the martensitic transformation temperature so as to control the temperature more accurately.
[0056] Since the present invention is an ultra-low carbon ultra-pure martensitic precipitation hardening stainless steel, the content of C, Mn, Si, N, etc. is low, which has no effect on the martensitic transformation temperature, so no excessive consideration is given during calculation. At the same time, the present invention takes into account that part of the nickel and aluminum elements combine to form a β-NiAl phase, and it is necessary to reduce the influence of these two elements on the martensitic transformation temperature in proportion. In addition, considering that most martensitic transformation temperature studies are mainly based on low-alloy structural steel, it is concluded according to the experience and data accumulation of the inventor that the martensitic transformation end temperature Mf=Ms-120, Ms=1317-45Cr-62Ni-30Mo-15Nb+20Al. The calculation empirical formula of the martensitic transformation temperature recorded in the existing literature (such as Liu Peng's "Progress in Research on Prediction of the Start Temperature of Martensitic Transformation of Steel", Materials Development and Application, 2015, 88-92.), because the above-mentioned element influence is not taken into account, the calculated temperature will produce a large calculation error.
[0057] Furthermore, within the chemical composition range of each element involved in the present invention, the martensitic transformation start temperature Ms is generally controlled above 140°C, and the martensitic transformation end temperature Mf is controlled above 20°C. Considering the temperature fluctuation caused by the chemical composition deviation in the actual production process, in order to reduce the risk of non-conformity, in actual production, the material will be cooled to below 0°C on the basis of cooling to 20°C, so as to reduce and eliminate the influence of retained austenite on tensile strength.
[0058] In the subsequent aging heat treatment process, in order to ensure that the copper-rich strengthening phase can be dispersed and precipitated to fully play a strengthening role, the aging temperature is controlled at 505-545°C and the holding time is 1-10 hours. If the temperature is too low and the time is too short, the strengthening phase cannot be dispersed and precipitated, which reduces the strengthening effect and fails to achieve the expected strength. If the temperature is too high and the time is too long, it is easy to cause the precipitate to coarsen and grow, and the ideal strengthening effect cannot be achieved.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] 1. The present invention adopts aluminum as the main strengthening element for precipitation hardening strengthening in the composition design, combines the addition of Nb element, and utilizes the composite strengthening method of precipitation strengthening plus carbide strengthening to obtain a strength exceeding , and strictly limits the content of S, P, Si, Mn, N, Ti, H, O elements, cooperates with the addition of Cr, Ni, and Mo elements to improve the corrosion resistance of steel, and strictly controls the relationship between Ni and Cr, Mo, and Al elements to meet Ni = (Cr + Mo) × 0.45 + Al × 2.15%, while being able to form β-NiAl strengthening phase to improve strength, it can also inhibit the precipitation of δ ferrite, so that the stainless steel bar can obtain ultra-high strength and high toughness, and can also reduce the difference in longitudinal and transverse impact energy. Conventional ultra-high strength steel strengthened with aluminum does not take into account the role of Ni element, and cannot control the impurity elements within such a low range.
[0061] 2. Based on the composition design, the present invention adopts high purity raw materials to be smelted under vacuum conditions during the smelting process, and adopts electromagnetic + gas mixed stirring method to quickly and thoroughly remove oxygen and nitrogen from molten steel during the smelting process, so as to avoid the generation of impurities during the smelting process. Subsequently, through purification and rapid cooling, a high-purity, defect-free, dense fine-grained steel ingot is obtained, and the impurity elements in the alloy are controlled within an extremely low range, thereby improving the toughness of stainless steel. Subsequently, a higher heating temperature (1200-1250°C) and a precise heat treatment control system are adopted to effectively control and eliminate the delta ferrite in the matrix through solid-state high-temperature equilibrium diffusion, thereby improving the isotropic consistency of the material.
[0062] The tensile strength of the stainless steel bar obtained by the invention is ≥1550MPa, the yield strength is ≥1415MPa, the elongation is ≥15%, the area shrinkage is ≥65%, the difference between the transverse and longitudinal impact energy AkU is ≤11%, and the fracture toughness KIC is ≥110MPa·m 1 / 2 , can be applied to the hydraulic field which has high requirements for strength, toughness and corrosion resistance, and can also be applied to the fields of aerospace, petroleum, chemical industry, energy and power. Especially in aerospace, the use of high-strength stainless steel instead of traditional high-strength steel not only increases the service life of the aircraft and shortens the maintenance cycle, but also reduces manufacturing costs and reduces environmental pollution. DETAILED DESCRIPTION
[0063] The present invention will be further described below in conjunction with the embodiments.
[0064] The composition of the steel of the embodiment of the present invention is shown in Table 1, Table 2 is the preparation process parameters of the steel of the embodiment of the present invention, and Table 3 is the performance parameters of the steel of the embodiment of the present invention.
[0065] In comparative example 1, copper element strengthening and electric furnace + electroslag smelting were used to obtain ingots. Since the smelting was carried out in the atmosphere, the content of various impurities was high. Therefore, it can be seen from the test results in Table 3 that the tensile strength was low, the size and content of inclusions were high, and the toughness was poor. If such aerospace parts with high manufacturing requirements are used, component cracking and aging problems are likely to occur, affecting the use and safety of aerospace vehicles.
[0066] Although aluminum element strengthening is used in Comparative Example 2, the ingot is obtained by smelting using induction + electroslag. Since there is no optimization treatment on the chemical composition and the heating and forging temperature of the ingot is relatively low compared with the present invention, its delta ferrite content is as high as 2%, the impact toughness in the longitudinal and transverse directions is quite different, and the isotropic consistency of the material is not good. Moreover, due to the smelting in the atmosphere, the content of various impurities is relatively high. Therefore, it can be seen from the test results in Table 3 that the size and content of the inclusions are relatively high, and the fracture toughness Kic value is relatively poor. If this type of aerospace components with high manufacturing requirements are used, component cracking and aging problems are prone to occur, affecting the use and safety of aerospace vehicles.
[0067] The high-strength stainless steel bar of the present invention can be applied to the fields of aerospace, petroleum, chemical industry, energy and power, which have high requirements for strength, toughness and corrosion resistance, due to its excellent corrosion resistance and mechanical properties. Especially in the field of aerospace, the use of high-strength stainless steel instead of traditional high-strength steel not only increases the service life of the aircraft and shortens the maintenance cycle, but also reduces the manufacturing cost and reduces environmental pollution.
[0068]
[0069]
[0070]
Claims
1. A high-toughness ultra-high-strength stainless steel bar, the components of which are as follows by weight: C: 0.025-0.045%, Cr: 12.00-13.00%, Mo: 1.8-2.3%, Al: 0.90-1.10%, Nb: 0.01-0.02%, S≤0.0015%, P≤0.01%, Si≤0.10%, Mn≤0.10%, N≤0.0015%, Ti≤0.01%, H≤0.0001%, O≤0.0008%, the remainder includes Fe and other inevitable impurities, and satisfies Ni=(Cr+Mo)×(0.42-0.45)+Al×2.
15.
2. The high-toughness ultra-high-strength stainless steel bar according to claim 1, characterized in that: The balance is Fe and other inevitable impurities.
3. The high-toughness ultra-high-strength stainless steel bar according to claim 1 or 2, characterized in that: The Ni=(Cr+Mo)×0.42+Al×2.
15.
4. The high-toughness ultra-high-strength stainless steel bar according to claim 1, 2 or 3, characterized in that: The content of delta ferrite in the microstructure of the stainless steel bar is ≤0.5%, and the grain size is ≥7 levels.
5. The high-toughness ultra-high-strength stainless steel bar according to claim 1, 2, 3 or 4, characterized in that: The tensile strength of the stainless steel bar is ≥1550MPa, the yield strength is ≥1415MPa, the elongation is ≥15%, the area shrinkage is ≥65%, the difference between the transverse and longitudinal impact energy AkU is ≤11%, and the fracture toughness is KIC≥110MPa·m 1 / 2 。 6. The method for preparing the high-toughness ultra-high-strength stainless steel bar according to any one of claims 1 to 5, characterized in that: The steps include: 1) Smelting and casting According to the composition smelting of claim 1, 2 or 3, raw iron with purity ≥ 99.9% and other pure metals are used as furnace charge, and the charge is melted by induction heating in a vacuum environment below 3Pa. The molten steel needs to be continuously stirred by electromagnetic + gas mixed stirring in a high-temperature refining stage of 1500-1600°C. Subsequently, the high-purity molten steel obtained above is poured into a cylindrical ingot mold in a vacuum environment to obtain an electrode rod; The electrode rod is purified in a copper crucible in a vacuum environment below 5 Pa by melting and solidifying. During the purification process, the inner and outer walls of the crucible are cooled by a composite cooling method of air cooling and water cooling to obtain a stainless steel ingot. 2) Billet forging The stainless steel ingot is heated to 1200-1250°C and kept warm for ≥15h, and then forged to obtain an intermediate forging billet; 3) Forging or rolling The intermediate forging billet is heated to 1050-1150°C, and the stainless steel bar is obtained by forging or rolling, and the total deformation ratio of the finished product is ≥6; 4) Solution treatment and cooling The solution temperature is 910-940℃, the solution time is ≥1h, after the heat preservation, it is taken out of the furnace and cooled to the martensitic transformation end temperature M f Below, M f =M s -120, Ms=1317-45Cr-62Ni-30Mo-15Nb+20Al; 5) Aging heat treatment The aging temperature is 505-545℃, and the aging time is 1-10h. After the insulation is completed, the steel is taken out of the furnace and air-cooled to room temperature.
7. The manufacturing method according to claim 6, characterized in that: In step 4), the mixture is cooled to below 0°C after being taken out of the furnace.
8. The manufacturing method according to claim 6 or 7, characterized in that: In step 4), an ice-water mixture is used for cooling.
Citation Information
Patent Citations
Martensite precipitation hardening stainless steel for structural member and manufacturing method thereof
CN101538686B
High-strength and high-toughness stainless steel material and preparation method thereof
CN106011684A